Beliefs and Tensions of Kindergarten Pre Service Students: a Three Case Longitudinal Study - Mireia Pérez Peitx (Multidisciplinary Journal for Education, Social and Technological Sciences, 2015)
This present work is part of a four-year-project related to the pre service teachers’ beliefs’ about initial literacy from the University of Barcelona. In particular, this paper presents the evolution of beliefs and tensions from the first to the second year of training from three pre service kindergarten students. The final aim of the project is to make proposals in order to improve teacher education. So far, it can be confirmed that beliefs are resistant to change but not immovable. Some core beliefs have been identified and they have incorporated new information acquired during the second year of training, specifically, from the practice. Furthermore, tensions and the awareness (or not) of them have become a very important issue since they show conflictive areas to work with students in order to make them conscious of their thoughts. In conclusion, beliefs and tensions appear to be the quid of the question in teacher education.